Translocation of soft phytoglycogen nanoparticles through solid-state nanochannels. Issue 41 (29th August 2019) - Lenart, William R.; Kong, Weiwei; Oltjen, William C.; Hore, Michael J. A.
Abstract : Phytoglycogen nanoparticles are soft, naturally-derived nanomaterials with a highly uniform size near 35 nm. Abstract : Phytoglycogen nanoparticles are soft, naturally-derived nanomaterials with a highly uniform size near 35 nm. Their interior is composed of a highly-branched polysaccharide core that contains more than 200% of its dry mass in water. In this work, we measure the translocation of phytoglycogen particles by observing blockade events they create when occluding solid-state nanochannels with diameters between 60 and 100 nm. The translocation signals are interpreted using Poisson–Nernst–Planck calculations with a "hardness parameter" that describes the extent to which solvent can penetrate through the interior of the particles. Theory and experiment were found to be in quantitative agreement, allowing us to extract physical characteristics of the particles on a per particle basis.